2001
DOI: 10.1152/ajprenal.0071.2001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrosative stress in acute renal ischemia

Abstract: First Published July 12, 2001; 10.1152/ajprenal.0071.2001.—Generation of reactive oxygen species and nitric oxide in hypoxia-reperfusion injury may form a cytotoxic metabolite, peroxynitrite, which is capable of causing lipid peroxidation and DNA damage. This study was designed to examine the contribution of oxidative and nitrosative stress to the renal damage in ischemic acute renal failure (iARF). iARF was initiated in rats by 45-min renal artery clamping. This resulted in lipid peroxidation, DNA damage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
253
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(271 citation statements)
references
References 57 publications
(65 reference statements)
7
253
0
11
Order By: Relevance
“…The effect was due to an attenuation of tubular injury, suggesting cytotoxic effects of NO produced by iNOS during renal ischemia. Similarly, the selective iNOS inhibitor L-N 6 -(1-iminoethyl)lysine (L-NIL) conferred renoprotective effects during ischemia (62). Selective iNOS inhibition with S-methyl-isothiourea prevented hypotension through systemic vasoconstriction and maintained cardiac output and reduced the signs of renal dysfunction in rats challenged with LPS (63).…”
Section: Inhibition Of Nitric Oxide Synthasementioning
confidence: 99%
“…The effect was due to an attenuation of tubular injury, suggesting cytotoxic effects of NO produced by iNOS during renal ischemia. Similarly, the selective iNOS inhibitor L-N 6 -(1-iminoethyl)lysine (L-NIL) conferred renoprotective effects during ischemia (62). Selective iNOS inhibition with S-methyl-isothiourea prevented hypotension through systemic vasoconstriction and maintained cardiac output and reduced the signs of renal dysfunction in rats challenged with LPS (63).…”
Section: Inhibition Of Nitric Oxide Synthasementioning
confidence: 99%
“…[4] Although all molecules are susceptible to ROS injury, lipids are targeted most frequently. Several studies have demonstrated that ROS can produce cellular injury by attacking membranes through peroxidation of polyunsaturated fatty acids that can alter both membrane structure and function of mitochondrial, lysosomal, and cell membrane via lipid peroxidation [1,5,6] . Malondialdehyde (MDA) is an end product of lipid peroxidation and widely accepted as a marker of ROS-mediated lipid peroxidation in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…3 Accumulation of protein-associated nitrotyrosine has been documented in inflammatory conditions of diverse origin such as atherosclerosis (1), respiratory disease (2), transplant rejection (3), multiple sclerosis (4), Alzheimer's disease (5), celiac disease (6), arthritis (7)(8)(9), ischemia-reperfusion injury (10), autoimmune diabetes (11), autoimmune uveitis (12), and infectious diseases (13). Although the precise molecular mechanism(s) responsible for in vivo formation of nitrotyrosine is still not firmly established, peroxynitrite and other reactive nitrogen species generated during periods of inflammation are thought to be primary intermediates (14,15).…”
mentioning
confidence: 99%